2022
DOI: 10.3390/genes13071103
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the GDSL Genes in Pecan (Carya illinoensis K. Koch): Phylogeny, Structure, Promoter Cis-Elements, Co-Expression Networks, and Response to Salt Stresses

Abstract: The Gly-Asp-Ser-Leu (GDSL)-lipase family is a large subfamily of lipolytic enzymes that plays an important role in plant growth and defense against environmental stress. However, little is known about their function in pecans (Carya illinoensis K. Koch). In this study, 87 CilGDSLs were identified and divided into 2 groups and 12 subgroups using phylogenetic analysis; members of the same sub-branch had conserved gene structure and motif composition. The majority of the genes had four introns and were composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(62 reference statements)
3
6
0
Order By: Relevance
“…The results highlighted notable differences in the structures of the 16 GELPs. Similar results were reported by Jiao et al. (2022) , in which the spatial structures of CilGDSL in pecans were also different.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results highlighted notable differences in the structures of the 16 GELPs. Similar results were reported by Jiao et al. (2022) , in which the spatial structures of CilGDSL in pecans were also different.…”
Section: Discussionsupporting
confidence: 89%
“…The results highlighted notable differences in the structures of the 16 GELPs. Similar results were reported by Jiao et al (2022), in which the spatial structures of CilGDSL in pecans were also different. Our molecular docking experiment revealed that the number of docking ligands varied greatly between individual proteins.…”
Section: The Molecular Mechanisms Of Gelps Functional Diversitysupporting
confidence: 89%
See 1 more Smart Citation
“…A crucial first step in transferring the knowledge acquired for model species to non-model species is homology identification. To date, the GELP family has been identified in diverse plant species including many with fully sequenced genomes, such as Arabidopsis thaliana (105 members) , Dasypyrum villosum (193) , Sedum alfredii (80), Nicotiana tabacum (159), Glycine max (194) , Oryza sativa (114) , Dendrobium catenatum (52), Carya illinoensis (87) , Zea mays (103) , Vitis vinifera (83), Brassica rapa (121), and six species in the Rosaceae family ( Pyrus bretschneideri , Malus domestica , Prunus mume , Prunus persica , Fragaria vesca and Prunus avium ; for a total of 597 GELP s) ( Chepyshko et al., 2012 ; Dong et al., 2016 ; Lai et al., 2017 ; Ding et al., 2019b ; Su et al., 2020 ; Lv et al., 2021 ; Wang et al., 2021 ; Zhang et al., 2021 ; Cenci et al., 2022 ; Jiao et al., 2022 ; Shen et al., 2022 ). Some GELP genes have been cloned and functionally characterized in B. napus , such as BnLIP2 ( Ling et al., 2006 ), Bn SCE3 ( Clauss et al., 2008 ), BnGDSL1 ( Ding et al., 2019a ), and BnSFAR1 - 5 ( Karunarathna et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout those habitats, pecans generally develop under a range of climatic conditions with complicated and volatile temperature ranges and cumulative precipitation during the growing season [ 24 , 26 ]. Meanwhile, climate change has also been altering the situation and a growing number of reports have been published on various responses of pecan to environmental factors to understand its decreased growth or survival [ 24 , 27 , 28 ]. Variety identification, including dramatic phenotypic and physiological diversifications, is one of the crop-domestication processes for increasing yield and high-quality crops [ 29 ].…”
Section: Introductionmentioning
confidence: 99%